Case studies : adaptive facade network - Aelenei, Laura Elena (2018)
ABSTRACT: Adaptive building envelopes can provide improvements in building energy efficiency and economics, through their capability to change their behaviour in real time according to indooroutdoor parameters. This may be by means of materials, components or systems. As such, adaptive façades can make a significant and viable contribution to meeting the EU´s 2020 targets. Several different adaptive façade concepts have already been developed, and an increase in emerging, innovative solutions is expected in the near future. In this context the EU initiative COST Action TU 1403 aims to harmonize, share and disseminate technological knowledge on adaptive facades at a European level. According to the definition given by this COST Action, an adaptive façade is a building envelope consisting of multifunctional and highly adaptive systems that is able to change its functions, features, or behaviour over time in response to transient performance requirements and boundary conditions, with the aim of improving the overall building performance. In order to explore the available and emerging technologies focusing on adaptive façades, Working Group 1 of the COST Action undertook research to form a database of adaptive façade case studies and projects structured in accordance with a simple classification – materials, components and systems. In addition to this, details of the purpose of the systems/components/materials with adaptive features and the working principle of each technology were also collected together with data regarding design practice, technology readiness, and economical aspects, among others. The information was collected with the help of a specific online survey (structured in the following main sections: detailed description - metrics- characterization- economic aspects – references). The database includes 165 cases of adaptive façade systems, components, and materials that allowed a variety of analyses to be carried out. According to the classification adopted within WG1 (materials, components, systems), each of the classification terms are introduced together with examples from the case study database in the following sections. This volume ends with a section dedicated to future developments, where different issues are addressed such as embedded functionality and efficiency amd biomimetic inspirations. The importance of adaptive façades through their flexibility, and intelligent design within the context of smart cities is also discussed.